C23-Carbazole Alkaloids from the bark of Murraya koenigii (L.) Spreng - Tan Siow Ping, Nafiah Mohd Azlan, Ahmad Kartini, (N/A, 2014)
C23-Carbazole Alkaloids from the bark of Murraya koenigii (L.) Spreng by Tan Siow Ping, Nafiah Mohd Azlan, Ahmad Kartini,